A methodological approach for the non-monetary valuation of ecosystem services in three communities of the Colombian Amazon - Durán H., Zulma; Arguello A., Heliodoro; Tapasco, Jeimar (Universidad Nacional de Colombia, 2016)
To conduct a non-monetary valuation of ecosystem services, this study explored combining data on the use of ecosystem resources with measuring the effort expended on agricultural activities in three communities of the lower Caqueta, Colombian Amazon. By measuring the energy expended by people during their principal subsistence activities, a measure of wellbeing was also indirectly obtained. For the three communities, the most costly ecosystem service in terms of energy expended was land in forests, which is prepared for planting with felling and clearing, with a value of 1,353 kcal per workday. This was followed by bush meat from hunting at 811 kcal per workday, fish at 682 kcal, obtaining food from the chagra (small family farming plot) at 470 kcal, collecting fruits at 380 kcal, collecting firewood at 148 kcal, and fetching water at 29 kcal. The preparation of casabe (cassava flatbread) as a cultural service has an energy cost of 386 kcal, while preparing mambe (toasted pulverized coca leaves) has a much higher cost at 808 kcal.